Early Warning Sistem Perusahaan Era Pandemi Covid-19 - Dwi Bhakti Iriantini; Soemaryono Soemaryono; Rudi Pratono (Owner : Riset dan Jurnal Akuntansi, 2022)
To break the chain of spread of the Covid-19 virus, the Government implemented a policy of restricting people's movements. The fact that occurred due to restrictions on community activities, the wheels of the economy were disrupted, even some business activities were closed. The formulation of the research problem, how are the results of the analysis of the Springate, Altman, Grover and Zmijewski Bankruptcy prediction models in the Covid-19 pandemic era. The purpose of the study was to empirically test the springate, altman, grover and zmijewski bankruptcy prediction models in companies during the covid-19 pandemic era. The research subjects are companies listed on the Indonesia stock exchange for the hotel, restaurant and tourism sub-sector in 2020. The results of the springate model test (s-score) show that 25 companies are predicted to have the potential to go bankrupt, 3 companies are predicted to be healthy. Altman model (Z-Score) shows that 16 companies are predicted to have the potential to go bankrupt, 4 companies experience a slight potential for bankruptcy and 4 companies are healthy. The grover model (G-Score) shows that 6 companies are predicted to have the potential to go bankrupt, 22 companies are healthy. The zmijewski model (X-Score) shows that 1 company is predicted to have the potential to go bankrupt, 27 companies are predicted to be healthy. The four models that show the same results for companies that are predicted to be healthy are PT. Asia Sejahtera Mina, Tbk with the issuer code AGAR.